Real-time rendering of light-scattering media - Zhou, Kun; Ren, Zhong; Lin, Steve; Guo, Baining; Shum, Harry (US Patent 8009168 B2, 2011)
A real-time algorithm for rendering of an inhomogeneous scattering media such as smoke under dynamic low-frequency environment lighting is described. An input media animation is represented as a sequence of density fields, each of which is decompressed into a weighted sum of a set of radial basis functions (RBFs) and an optional residual field. Source radiances from single and optionally multiple scattering are directly computed at only the RBF centers and then approximated at other points in the volume using an RBF-based interpolation. Using the computed source radiances, a ray marching technique using slice-based integration of radiance along each viewing ray is performed to render the final image. During the ray marching process, the residual field may be compensated back into the radiance integral to generate images of higher detail.